Impact of weight reduction practices on overall competition placement in international judo athletes - Stefanovsky, M.; Neshoda, D.; Kracek, S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Background. Practices used in body weight (BW) reduction by judo athletes may have a negative impact on their sports performance and overall rankings in competitions.